(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the content and essence of the concept of bioethical knowledge, the pedagogical necessity of its formation, as well as bioethics, which is a complex component of modern culture, and the sciences that study the ethical consequences of the achievements of science nd biomedical technologies, are described in this article.